2021
DOI: 10.1029/2020wr029389
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the Comment on “Tu et al., an Analytical Solution of Groundwater Flow in a Confined Aquifer With a Single‐Well Circulation System, Water Resources Research, First Published: 12 June 2020.”

Abstract: We would like to thank Dr. Kabala for his interest in our work and his Comment on it and appreciate the opportunity to clarify and address his concerns. The idea of employing a single-well circulation groundwater heat-pump system (as shown in Figure 1) to provide heating or cooling of buildings was first presented by Sorensen and Reffstrup (1992). Our work is based on the conceptual model of Sorensen and Reffstrup (1992) and the analytical solution developed for this system by Ni et al. (2011). We have to admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In order to improve the overall environment of river lake connected areas and promote urban ecological water conservancy construction, the improvement of urban river lake water environment has become a research hotspot [2][3][4] . Tu Huawei et al established an integrated water environment model of "land unit river network lake", simulated and analyzed the water quality improvement effects of various water environment improvement schemes in the Jinshan Lake area of Huizhou City, and showed that implementing source control and pollution interception projects can effectively improve water quality conditions [5] ; Zhou Si et al showed through regular monitoring of the water quality and plankton in Mingxin Lake that real-time ecological governance projects can significantly improve water transparency and reduce eutrophication index [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the overall environment of river lake connected areas and promote urban ecological water conservancy construction, the improvement of urban river lake water environment has become a research hotspot [2][3][4] . Tu Huawei et al established an integrated water environment model of "land unit river network lake", simulated and analyzed the water quality improvement effects of various water environment improvement schemes in the Jinshan Lake area of Huizhou City, and showed that implementing source control and pollution interception projects can effectively improve water quality conditions [5] ; Zhou Si et al showed through regular monitoring of the water quality and plankton in Mingxin Lake that real-time ecological governance projects can significantly improve water transparency and reduce eutrophication index [6] .…”
Section: Introductionmentioning
confidence: 99%